Identifying and expression analysis of WD40 transcription factors in walnut. Issue 3 (29th July 2022) - Chen, Shuwen; Li, Dapei; Chen, Sisi; He, Jianing; Wang, Zengbin; Yang, Guiyan; Lu, Zhoumin
Abstract: Walnut ( Juglans regia L.) is an important woody oil plant and will be affected by abiotic and biological stress during its growth and development. The WD‐repeat (WD40) protein is widely involved in plant growth, development, metabolism, and abiotic stress response. To explore the stress response mechanism of walnut, based on the complete sequencing results of the walnut genome, this study identified and analyzed the physiological, biochemical, genetic structure, and conservative protein motifs of 42 JrWD40 genes, whose expression to abnormal temperature were tested to predict the potential biological function. The results showed that the open reading frame (ORF) of these WD40 genes were 807–2, 460 bp, encoding peptides were 29, 610.55–90, 387.98 Da covering 268–819 amino acids, as well as 12–112 phosphorylation sites. JrWD40 proteins were highly conserved with four to five WD40 domains and shared certain similarity to WD40 proteins from Arabidopsis thaliana (L.) Heynh. JrWD40 genes can be induced to varying degrees by low and high temperature treatments. JrWD40 ‐ 32, JrWD40 ‐ 27, JrWD40 ‐ 35, and JrWD40 ‐ 21 are affected by high temperature more seriously and their expression levels are higher; while JrWD40 ‐ 37, JrWD40 ‐ 26, JrWD40 ‐ 20, JrWD40 ‐ 24, and other genes are inhibited under low temperature stress. JrWD40 ‐ 40, JrWD40 ‐ 28, and JrWD40 ‐ 18 were first suppressed with low expression, while as the treatment time prolonging, the expression level was increased under cold condition. JrWD40 ‐ 14, JrWD40 ‐ 18, JrWD40 ‐ 34, and JrWD40 ‐ 3 displayed strong transcriptions response to both heat and cold stress. These results indicated that JrWD40 genes can participate in walnut adaptation to adversity and can be used as important candidates for walnut resistance molecular breeding. Core Ideas: The woody plant (walnut) WD40 protein was identified. Whether the walnut WD40 transcription factor responds to abiotic stress was investigated. Some WD40 transcription factors were significantly induced by temperature stress.